COVID-19: years of life lost (YLL) and saved (YLS) as an expression of the role of vaccination - Hulíková Tesárková, Klára; Dzúrová, Dagmar (Scientific reports, 2022)
When evaluating vaccine efficacy, the conventional measures include reduction of risk of hospitalization and death. The number of patients dying with or without vaccination is often in the public spotlight. However, when evaluating public health interventions or the burden of disease, it is more illustrative to use mortality metrics taking into account also prematurity of the deaths, such as years of life lost (YLL) or years of life saved (YLS) thanks to the vaccination. We develop this approach for evaluation of the difference in YLL and YLS between COVID-19 victims with or without completed vaccination in the autumn pandemic wave (2021, October-December) in Czechia. For the analysis, individual data about all COVID-19 deaths in the country (N = 5797, during the studied period) was used. While 40.6% of the deaths are in cohorts with completed vaccination, this corresponds to 35.1% of years of life lost. The role of vaccination is expressed using YLS and hypothetical numbers of deaths. The registered number of deaths is approximately 3.5 times lower than it would be expected without vaccination. The results illustrate that vaccination is more effective in saving lives than suggested by simplistic comparisons.
Keywords: pandemie; COVID-19; Pandemics; Public Health; vakcinace; Humans; Life Expectancy; veřejné zdravotnictví; lidé; naděje dožití; Vaccination